The development of sand erosion induced by shield-tunnel joint leakage. (June 2023) - Li, Rujia; Lei, Huayang; Ma, Changyuan; Liu, Yingnan; Liu, Ningmin
Highlights: Visualized model tests are adopted to simulate the tunnel joint leakage with different water environments. The damage evolutional process of sand erosion and erosion void are investigated in the model tests. The theoretical model is proposed to predict the volumetric flow rate of the sand erosion and the volume of the erosion void. Abstract: Sand erosion induced by shield-tunnel joint leakage is one of the most frequent catastrophes, causing ground collapses and tunnel failures. In this paper, a self-designed test device that considers differences in water head, burial depth and leaky joint characteristics was used to investigate sand erosion and void development. The experimental results show that the development of sand erosion has obvious temporal and spatial evolution characteristics. In the temporal dimension, sand erosion development can be divided into four stages: vertical erosion, cavity formation, coarse-particle skeleton distribution (CPSR) and steady seepage. In the spatial dimension, it can be divided into three regions: the stable zone, slip surface and eroded zone shape. It is found that the erosion zone can be described by a rotating ellipsoid and the scope of the erosion zone increases with increasing water head, whereas the influence of the burial depth is not significant. The influence of the invert leakage on the volume flow rate is also determined to be larger than that of the vault leakage and the volume flow rate rapidly increases when the size of the leaky joint exceeds the critical outlet size. Finally, a theoretical model based on the test results is proposed to predict the volumetric flow rate of sand erosion.